2018
DOI: 10.1038/s41598-018-26216-8
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in a diverse beetle assemblage along two elevational gradients in the Australian Wet Tropics

Abstract: Altered abiotic conditions resulting from human-induced climate change are already driving changes in the spatial and temporal distributions of many organisms. For insects, how species are distributed across elevations is relatively well known, but data on their seasonality at different elevations are lacking. Here we show seasonal variation in beetle abundance and species richness along two spatially-distinct elevational transects (350–1000 m and 100–1000 m asl) in the rainforests of northern Australia. Tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 45 publications
1
25
1
Order By: Relevance
“…Janzen () showed beetle diversity to decrease in mid‐elevations during the wet season, while he found no seasonal shift of heteropteran diversity in Costa Rica. The only more recent study was performed in the wet tropics of Australia (Wardhaugh et al, ). Despite the strong effect of seasonality on species richness and abundance of beetles, both peaking during the high wet season, no consistent seasonal shifts of beetles abundance or species richness along elevation were observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Janzen () showed beetle diversity to decrease in mid‐elevations during the wet season, while he found no seasonal shift of heteropteran diversity in Costa Rica. The only more recent study was performed in the wet tropics of Australia (Wardhaugh et al, ). Despite the strong effect of seasonality on species richness and abundance of beetles, both peaking during the high wet season, no consistent seasonal shifts of beetles abundance or species richness along elevation were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Such phenological changes of tropical lepidopteran communities are often driven by wet and dry season cycles influencing availability of resources for both caterpillars and adult butterflies and moths (Grøtan, Lande, Chacon, & DeVries, 2014;Grøtan, Lande, Engen, Saether, & DeVries, 2012;Maicher et al, 2018;Valtonen et al, 2013). In contrast, montane insect phenology is crucially driven by seasonal changes of temperature (Bishop, Robertson, van Rensburg, & Parr, 2014;Boulter, Lambkin, & Starick, 2011;Wardhaugh, Stone, & Stork, 2018). Divergent pressures on communities at different elevations might substantially influence the spatial distribution of species diversity along elevation, as well as its temporal dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…a higher species richness and abundance was recorded in the rainy season in a study conducted in India (Arya and Tamta 2016). A distinct peak in abundance during the summer wet-season was also found by Wardhaugh et al (2018) even though the authors found that temperature was the best predictor of abundance and species richness in their study from Northern Australia, while rainfall had little influence. An interesting finding of the present study was further that the observed increase in species diversity in the less disturbed forest was more pronounced in the window traps, suggesting that beetles with larger flight movements are profiting more from the less disturbed forest than others such as those mostly walking on the ground.…”
Section: Discussionmentioning
confidence: 58%
“…The division of the main drivers nevertheless represents a great challenge, depending on their inter-connectedness. Indeed, both temperature and elevational area have previously been identified as major factors influencing numbers of species and community structure (Bishop et al 2014;Wardhaugh et al 2018). However, historical factors, i.e., climate change, niche conservatism, orogenesis, and immigration and evolutionary mechanisms (speciation and radiation), need to be considered (Plant 2009;Plant et al 2011Plant et al , 2012Graham et al 2014;Merckx et al 2015) in addition to ecological explanations.…”
Section: Discussionmentioning
confidence: 99%